Implementation of SAVI Learning Model Through Practicum Activities Towards Students Science Learning Outcomes (Journal of Primary Education, 2019)
The study aims to explain the influence of implementation of SAVI learning models through practicum activities toward 4th-grade students outcomes in science learning. The research methodology used was quasi-experimental with the nonequivalent pretest-posttest control group design. The research results show that the implementation of SAVI learning has a significant influence on improving cognitive, affective, and psychomotor of students. The cognitive, affective, and psychomotor aspect of a student of practicum class gained better scores than that of the control class. It was indicated from the treatment by using the SAVI learning model through practicum activities in the experimental class while the control class was treated using the expository model. The affective domain learning outcomes achieved scores of 83.7; the cognitive domain learning outcomes with 76.48 points and psychomotor domain learning outcomes get scores of 84. Based on the results of the research that has been obtained, it can be concluded that the ability of students to conclude the results of the practicum can be improved by using the application of the SAVI learning model.